Characteristics of Highly Birefringent Photonic Crystal Fiber with Defected Core and Equilateral Pentagon Architecture. (29th August 2016) - Yu, Fei; Wang, Zhenpeng; Yang, Wenhao; Lv, Chongyang
Abstract : A novel high birefringence and nearly zero dispersion-flattened photonic crystal fiber (PCF) with elliptical defected core (E-DC) and equilateral pentagonal architecture is designed. By applying the full-vector finite element method (FEM), the characteristics of electric field distribution, birefringence, and chromatic dispersion of the proposed E-DC PCF are numerically investigated in detail. The simulation results reveal that the proposed PCF can realize high birefringence, ranging from 10 - 3 to 10 - 2 orders of magnitude, owing to the embedded elliptical air hole in the core center. However, the existence of the elliptical air hole gives rise to an extraordinary electric field distribution, where a V-shaped notch appears and the size of the V-shaped notch varies at different operating wavelengths. Also, the mode field diameter is estimated to be about 2 μ m, which implies the small effective mode area and highly nonlinear coefficient. Furthermore, the investigation of the chromatic dispersion characteristic shows that the introduction of the elliptical air hole is helpful to control the chromatic dispersion to be negative or nearly zero flattened over a wide wavelength bandwidth.